Recognition and enforcement of foreign arbitral awards : a concise guide to the New York Convention's uniform regime - Ferrari, Franco; Rosenfeld, Friedrich; Kotuby, Charles T. (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Publishing, 2023)
"This incisive book is an indispensable guide to the New York Convention's uniform regime on recognition and enforcement of foreign arbitral awards. Framing the Convention as a uniform law instrument, the book analyses case law from major arbitration jurisdictions to explain its scope of application, the duty to recognize arbitral agreements and awards as well as their limitations, and the procedure and formal requirements for enforcing arbitral awards. Combining insight from arbitration practice with perspectives from private international law, the book underlines the importance of the Convention's foundation in a treaty of international law, arguing that this entails a requirement to interpret the key concepts it sets forth based on international law rules of interpretation. However, it also demonstrates where municipal laws are relevant and discusses the private international law principles through which these instances can be identified. Addressing one of the core treaties of international arbitration, this will be crucial reading for legal practitioners and judges working in the field. It will also prove valuable to scholars and students of commercial and private international law, particularly those focused on cross-border disputes and arbitration"--
Includes bibliographical references and index.
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards -- (1958 June 10); International commercial arbitration; Judicial assistance